IMPROVEMENT OF SERVICE OFFERING LINKED WITH CUSTOMER SATISFACTION IN THE POWER ELECTRONICS FIELD - Sahebi, Daniel (My University, 2013)
Importance of production strategy in the 21st century in global business is growing. This paper supports the view that dynamic capabilities can be used successfully for improving company’s efficiency. Effective information flow, flexibility, speed and responsiveness need more focus in a fast changing world. Delivery accuracy is the key, while short delivery time is a competitive factor. This Thesis is a case study research related to customer satisfaction, which focuses on more effective service improvement and changes in regards with meeting the customer needs. Through empirical approach and related enterprises investigation, based on employees' perspective and end-user’ perspective, it designs a questionnaire system to collect data. In a case company, totally 31 interviews were made from 18 subsidiaries and 13 from end customers. Finally, we use statistical analysis to analyze the collected data and draw a conclusion. This thesis may help manufacturing firms to improve their value added services in addition to operating closer to their global customers. The main focus of this thesis is on power electronics business segments. To make wider conclusions, more empirical studies are needed. The results of this thesis may bring additional value to the previous studies regarding company strategy, Business environment, Innovativeness and operational excellence.
Keywords: Overall customer satisfaction; service offering; service quality improvement; effective information flow; dynamic capabilities.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|